Efficacy and safety of intravitreal injection of aflibercept biosimilar for treating diabetic macular edema - Zhai, Gaixia; Sun, Chao; Zhang, Xia; Su, Yuanzhen (Frontiers in Medicine, 2025)
PurposeThis study aimed to evaluate the efficacy and safety of intravitreal injection of aflibercept biosimilar in the treatment of diabetic macular edema (DME).MethodsClinical data were collected from 33 patients (40 eyes) newly diagnosed with DME in the ophthalmology department of our hospital between February and April 2024, all of whom were treated with the aflibercept biosimilar. Patients were managed according to the 3+ Pro re nata (PRN) regimen and completed a minimum follow-up period of 6 months. The best-corrected visual acuity (BCVA) testing, optical coherence tomography, optical coherence tomography angiography, and multifocal electroretinography were performed before and after treatment. BCVA and central retinal thickness (CRT) were compared at baseline and 1-, 3-, and 6-months post-treatment. Additionally, the changes in the foveal avascular zone area, vascular density (VD) of superficial and deep retinal capillaries in the macular region, and the first positive peak amplitude density in ring 1 were analyzed 6 months post-treatment.ResultsBCVA improved significantly from 0.53 ± 0.12 logMAR at baseline to 0.31 ± 0.12, 0.26 ± 0.10, and 0.26 ± 0.08 logMAR at 1-, 3-, and 6-months post-treatment, respectively, (p < 0.05). CRT decreased significantly from 422.4 ± 63.04 μm at baseline to 294.7 ± 47.89, 272.1 ± 47.43, and 281.0 ± 40.72 μm at 1-, 3-, and 6-months post-treatment, respectively, (p < 0.05). The foveal avascular zone area significantly reduced from 0.40 ± 0.08 mm2 at baseline to 0.35 ± 0.07 mm2 at 6 months post-treatment. Superficial VD increased significantly from 38.90 ± 7.88% at baseline to 41.21 ± 7.98% at 6 months post-treatment, while deep VD significantly increased from 35.67 ± 7.50% at baseline to 38.72 ± 6.90% (p < 0.05). The first positive peak amplitude improved significantly from 55.30 ± 9.45 to 72.90 ± 7.44 nv/deg2 at 6 months post-treatment (p < 0.05).ConclusionIntravitreal injections of aflibercept biosimilar can significantly reduce DME, improve BCVA, enhance macular perfusion, and restore macular function.